Serum Vitamin D Levels Are Associated With Increased COVID-19 Severity and Mortality Independent of Whole-Body and Visceral Adiposity - Vanegas-Cedillo, Pablo Esteban; Bello-Chavolla, Omar Yaxmehen; Ramírez-Pedraza, Natalia; Rodríguez Encinas, Bethsabel; Pérez Carrión, Carolina Isabel; Jasso-Ávila, María Isabel; Valladares-García, Jorge Carlos; Hernández-Juárez, Diana; Vargas-Vázquez, Arsenio; Antonio-Villa, Neftali Eduardo; Chapa-Ibarguengoitia, Monica; Ponce de Leon, Alfredo; et al. (Frontiers in Nutrition, 2022)
INTRODUCTION: Coronavirus disease (COVID-19) is a global pandemic. Vitamin D deficiency has been associated with susceptibility to infectious disease. In this study, the association between COVID-19 outcomes and vitamin D levels in patients attending a COVID-19 reference center in Mexico City are examined. METHODS: Consecutive patients with confirmed COVID-19 were evaluated. All patients underwent clinical evaluation and follow-up, laboratory measurements and a thoracic computerized tomography, including the measurement of epicardial fat thickness. Low vitamin D was defined as levels <20ng/mL (<50nmol/L) and deficient Vitamin D as a level ≤12ng/mL (<30nmol/L) RESULTS: Of the 551 patients included, low vitamin D levels were present in 45.6% and deficient levels in 10.9%. Deficient Vitamin D levels were associated with mortality (HR 2.11, 95%CI 1.24-3.58, p=0.006) but not with critical COVID-19, adjusted for age, sex, body-mass index and epicardial fat. Using model-based causal mediation analyses the increased risk of COVID-19 mortality conferred by low vitamin D levels was partly mediated by its effect on D-dimer and cardiac ultrasensitive troponins. Notably, increased risk of COVID-19 mortality conferred by low vitamin D levels was independent of BMI and epicardial fat. CONCLUSION: Vitamin D deficiency (≤12ng/mL or <30nmol/L), is independently associated with COVID-19 mortality after adjustment for visceral fat (epicardial fat thickness). Low vitamin D may contribute to a pro-inflammatory and pro-thrombotic state, increasing the risk for adverse COVID-19 outcomes.